2013
DOI: 10.2196/jmir.2243
|View full text |Cite
|
Sign up to set email alerts
|

If We Offer it, Will They Accept? Factors Affecting Patient Use Intentions of Personal Health Records and Secure Messaging

Abstract: BackgroundPersonal health records (PHRs) are an important tool for empowering patients and stimulating health action. To date, the volitional adoption of publicly available PHRs by consumers has been low. This may be partly due to patient concerns about issues such as data security, accuracy of the clinical information stored in the PHR, and challenges with keeping the information updated. One potential solution to mitigate concerns about security, accuracy, and updating of information that may accelerate tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 40 publications
9
77
1
Order By: Relevance
“…Although growing patient demand to online personal health record (PHR) access was already recognized in other studies [25,[31][32][33], it is still not widely adopted. A study among 283 individuals over the age of 18 found that individual factors (satisfaction with provider, belief of the tool to be empowering) and environmental factors (communication tactics, technology characteristics and management support) influence intentions to use a PHR [34]. These aspects should be taken into account with the implementation of PHRs.…”
Section: Discussionmentioning
confidence: 99%
“…Although growing patient demand to online personal health record (PHR) access was already recognized in other studies [25,[31][32][33], it is still not widely adopted. A study among 283 individuals over the age of 18 found that individual factors (satisfaction with provider, belief of the tool to be empowering) and environmental factors (communication tactics, technology characteristics and management support) influence intentions to use a PHR [34]. These aspects should be taken into account with the implementation of PHRs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic conditions have more office visits, laboratory and procedural tests, and selfmanagement needs. 40,41 Although critics express concerns that online technologies might discriminate against older patients, 42,43 1 out of 3 patients aged 60 to 69 years enrolled, the highest use rate by any age-group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic conditions have more office visits, laboratory and procedural tests, and selfmanagement needs. 40,41 Although critics express concerns that online technologies might discriminate against older patients, 42,43 1 out of 3 patients aged 60 to 69 years enrolled, the highest use rate by any age-group.Black and Hispanic patients were less likely to use the IPHR. Even though prior studies document a digital divide in use of personal health records among at-risk populations, 44 the growing ubiquity of mobile devices is closing the digital divide, 45 and greater use of these very technologies is being discussed to narrow health inequities.…”
mentioning
confidence: 99%
“…that is associated with multiple interactions among varying users (e.g., patients, providers, insurance companies), complex health information and systems (e.g., labs, medications, insurance), and advanced health information technology tools (e.g., personal health records, personal health devices) [2][3][4]. In PHIM research, little is known about college students' information management activities in the health context.…”
Section: Personal Health Information Management (Phim) Is a Special Cmentioning
confidence: 99%
“…records, to fulfill their health information needs [2][3]. For a narrower scope of personal health documents, trained hospital records managers in direct patient care or billing have conventionally performed some of these activities.…”
mentioning
confidence: 99%